Universal Numeric Quantifiers in Japanese - Ochi, Masao (IBERIA: An International Journal of Theoretical Linguistics, 2014)
This paper examines a subtype of floating quantifiers, in which a universal quantifier along with a numeral appear at a distance from their nominal associate. According to Cirillo (2010), this floating universal numeric quantifier (UNQ) construction is found in some (but not all) Romance and Germanic languages. While Cirillo provides strong evidence for a stranding analysis (cf. Sportiche, 1988; Bošković, 2004) of the floating UNQ rather than an adverbial approach (cf. Bobaljik, 2004; Nakanishi, 2006), his most crucial data could be accommodated under a particular version of the adverbial view, advocated by Doetjes (1997) and Fitzpatrick (2006), which postulates pro inside a base-generated adjunct nominal. Building on Kawashima’s (1994; 1998) observations about Japanese, this paper argues that (i) Japanese also has the adnominal/floating UNQ and (ii) the stranding approach is superior to the pro-based adverbial analysis noted above in handling the floating UNQ. To show this, I will examine in some depth the syntax of adnominal quantification in Japanese (and Chinese) with a special focus on the ways in which numeral classifiers interact with other adnominal elements. Several theoretical consequences of the analysis will be explored, including the nature of quantifier stranding and syntactic locality.